Performance of the FRPC rehabilitated RC beamcolumn joints subjected to cyclic loading - Mukherjee, Abhijit; Jain, K. (Associated Cement Companies Ltd., 2015)
This paper discusses both experimental and analytical investigations for evaluation of the performance of the fiber reinforced polymer composites (FRPC) rehabilitated reinforced concrete (RC) beam-column joints subjected to cyclic loading. For experimental investigations, two types of beam-column joint specimens, with ductile and brittle reinforcement detailing are cast and investigated in this study. The joint specimens are subjected to the cyclic displacements of increasing amplitude until failure. Post failure, the joint specimens are rehabilitated using FRPC. The rehabbed joint specimens are then subjected to the similar regime of cyclic displacements until failure. Salient details of the procedures for preparation and investigation of both control and rehabbed joint specimens are discussed in this paper. Performances of joint specimens are recorded in form of the load-displacement plots. Comparisons between performances of control and rehabbed joint specimens highlight the efficiency of the discussed rehabilitation scheme in enhancement of strength, ductility, and deformability of RC beam-column joints. In analytical investigations, the load displacement relationships for both control and rehabbed joints are modeled in form of the multi-scale models which consider stiffness degradation under cyclic loading. Accordingly, this paper also reports brief discussion on the stepwise development of the analytical models for performance of the materials; the cross-section; and that of the joints. Good agreement between experimentally observed and analytically modeled load-displacement relations facilitates validation of the analytical models, which then provides useful means for field applications of FRPC in rehabilitation of RC beam-column joints.